Peirce's Inkstand as an External Embodiment of Mind. - Skagestad, Peter (Transactions of the Charles S. Peirce Society)
Deals with the importance of a passage from philosopher Charles Peirce. Details on the symbolism of Peirce's inkstand and its relation to thinkers; Cognitive role of mathematical notation; Discussion on orality-literacy transformation.